2020
DOI: 10.1186/s12864-020-06948-6
|View full text |Cite
|
Sign up to set email alerts
|

HAK/KUP/KT family potassium transporter genes are involved in potassium deficiency and stress responses in tea plants (Camellia sinensis L.): expression and functional analysis

Abstract: Background Tea plant is one of the most important non-alcoholic beverage crops worldwide. While potassium (K + ) is an essential macronutrient and greatly affects the growth and development of plants, the molecular mechanism underlying K + uptake and transport in tea plant root, especially under limited-K + conditions, is still poorly understood. In plants, HAK/KUP/KT family members play a crucial role in K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 83 publications
1
24
0
Order By: Relevance
“…In addition, we found that the expression levels of some SeKUPs differed between shoots and roots, and that some SeKUPs were greatly suppressed under salt treatments. This is similar to Camellia sinensis ( CsHAK17 ) ( Yang et al, 2020 ), implying that they are not sensitive to high NaCl and K + deficiency.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, we found that the expression levels of some SeKUPs differed between shoots and roots, and that some SeKUPs were greatly suppressed under salt treatments. This is similar to Camellia sinensis ( CsHAK17 ) ( Yang et al, 2020 ), implying that they are not sensitive to high NaCl and K + deficiency.…”
Section: Discussionsupporting
confidence: 54%
“…The qRT-PCR was performed on a BioRad CFX96 real-time system, with a SYBR Green Master Mix kit (TaKaRa Biotechnology, Dalian, China), according to the manufacturer’s instructions. The components of the PCR mixture were as follows: 10 μL of 2× SYBR Premix ExTaq, 0.4 μL of each 10 μM forward and reverse primers, and 1 μL of the cDNA (150 ng) template, in 20 μL total volume . Three biological replicates of each sample were used, and the data are presented as mean ± standard error (SE) ( n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…A crucial ecological aspect of K + is how plants can adapt to low-K-availability soils. Current experimental studies have observed that high-affinity K + transporters are mediators of K + stress responses [ 220 ]. Higher plants can adapt to drought stress by producing higher numbers and concentrations of amino acids and organic acids in the cell solution to replace the lack of K + for osmotic adjustment coupled with its negative effect on plant growth and reserve accumulation [ 213 ].…”
Section: Role Of K In Terrestrial Ecosystemsmentioning
confidence: 99%
“…Recently, it has been found that the overexpression of several genes related to K + transporters and channels can increase the tolerance to K + deficiency. Among these, we can highlight the gene OsPRX2, which causes stomata closure [ 315 ]; the gene HAK, which is directly related to K + uptake under low soil K + availability [ 220 ]; or genes related to root elongation favoring higher K + uptake [ 316 ]. Thus, there is a great opportunity to genetically improve several crop species to improve potassium-use efficiency and help solve the problem of K + scarcity in soils and the access to potassium fertility in future markets [ 123 , 272 ].…”
Section: K and Food Security And Human Healthmentioning
confidence: 99%